2011
DOI: 10.1111/j.1476-5381.2011.01419.x
|View full text |Cite
|
Sign up to set email alerts
|

Methyl jasmonate down-regulates survivin expression and sensitizes colon carcinoma cells towards TRAIL-induced cytotoxicity

Abstract: BACKGROUND AND PURPOSEMethyl jasmonate (MJ) is a plant stress hormone with selective cytotoxic anti-cancer activities. The TNF-related apoptosis-inducing ligand (TRAIL) death pathway is an attractive target for cancer therapy. Although TRAIL receptors are specifically expressed in primary cancer cells and cancer cell lines, many types of cancer cells remain resistant to TRAILinduced cytotoxicity. Here we have assessed a possible synergy between MJ and TRAIL cytotoxicity in colorectal cancer (CRC) cell lines. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 42 publications
(67 reference statements)
0
25
0
Order By: Relevance
“…In the present study, it was revealed that the anticancer effect of methyl jasmonate downregulates Wnt/β-catenin expression in human colorectal cancer cells. Raviv et al (28) previously reported that methyl jasmonate downregulated survivin expression and sensitized colon carcinoma cells through the β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was revealed that the anticancer effect of methyl jasmonate downregulates Wnt/β-catenin expression in human colorectal cancer cells. Raviv et al (28) previously reported that methyl jasmonate downregulated survivin expression and sensitized colon carcinoma cells through the β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that down-regulation or inactivation of pro-survival proteins, including survivin and Bcl-2 [23], promotes anti-cancer efficacy or sensitizes tumor cells toward chemotherapeutic drugs in human tumor cells [24]. …”
Section: Resultsmentioning
confidence: 99%
“…However, the expression level of survivin was remarkably reduced in nemadipine-A treated cells. It has been well documented that the down-regulation of survivin by chemotherapeutic agents sensitizes cancer cells to TRAIL-induced apoptosis (Kim et al ., 2004; Lu et al ., 2008; Raviv et al ., 2011). Consistently, we have also found that nemadipine-A potentiates TRAIL-induced apoptosis by reducing survivin expression.…”
Section: Discussionmentioning
confidence: 99%